Impact Analysis of Planning and Design Elements on Urban Rail Transit Energy Consumption - GUO Yingjie; CHEN Xiaohong; LIU Haobing (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] By establishing an energy consumption model for urban rail transit, the impact of planning and design elements on its energy consumption is analyzed, so as to guide the optimization of urban rail transit planning and design schemes from the perspective of low-carbon and energy conservation. [Method] Taking the train traction energy consumption per unit operating mileage and the power and lighting energy consumption of stations per unit time as dependent variables, and taking relevant planning and design elements, line operation, and passenger flow intensity as independent variables, the impact of planning and design elements on the energy consumption of urban rail transit is estimated through structural equation models and random coefficient models. [Result & Conclusion] Planning and design elements have a significant impact on the energy consumption of urban rail transit, with the maximum impact reaching 35% of the traction energy consumption per vehicle-kilometer. At the same time, the above impact on the energy consumption of underground stations is greater than that on elevated stations, and the impact on the energy consumption of transfer stations is greater than that on non-transfer stations. Ignoring the indirect impact of planning and design elements on energy consumption will lead to an underestimation of their impact on the energy consumption of urban rail transit. To maximize the energy-saving potential of urban rail transit, it is necessary to maximize the proportion of elevated sections of the line and reasonably determine the station spacing on the basis of considering the urban land use space.